(untitled) (Fiep Bulletin - online, 2014)
The objective of the study was to determine the profile of motor performance children’s in the age group from seven to ten years, of both sexes, regularly enrolled in schools of the municipal net of teaching of the city of Manaus. The sample was constituted of 1904 male and 1974 female, selected at random, belonging to twenty schools of the area east of the city of Manaus. The tests of motor performance used were: a) standing long jump test; b) modified pull-up-test; and e) 30 meter-run test. The results of the present study allowed concluding that the tests of motor performance demonstrate significant differences between boys and girls, in most of the tests.